PERSEPSI IBU HAMIL DALAM PEMERIKSAAN HIV/AIDS DI BANYUMAS - Evicenna Naftuchah Riani; Dewi Ambarwati (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2020)
Human Immunodeficiency Virus / Acquired Immunodeficiency Syndrome (HIV / AIDS) is still a global problem, including in Indonesia. Where the morbidity and mortality rate have to increase. HIV is a virus that attacks the human immune system, so sufferers are susceptible to various diseases. AIDS is a collection of symptoms and infections resulting from damage to the human immune system caused by HIV infection. Finding of HIV / AIDS cases in Banyumas, has increased cases from year to year. In 2015, there were 251 HIV cases and 125 AIDS cases. Case data in Banyumas is derived from the VCT (Voluntery Counseling and Test) report from general Hospital Prof. Dr. Margono Soekardjo and RSUD Banyumas. This research uses a qualitative method with a case study. Data collection used indepth interviews of 8 primary informants and 12 secondary informants as triangulation. The results showed that health care workers in this case midwives did not maintain patient privacy, did not carry out pre and post counseling. HIV / AIDS testing is based on the Health Workers Initiative, and the implementation of integrated examinations in integrated ANC services. There is a gap between theory and implementation in the field.